Design Research: Development of Learning Trajectories in Realistic Mathematics Education on Relation and Function Materials - Gavrilla Mei Sela Marande; Hafsah Adha Diana (Indo-MathEdu Intellectuals Journal, 2023)
The purpose of this study is to produce a learning trajectory on the material of relations and functions in class VIII. This type of research is Design Research proposed by Gravemeijer & Cobb, carried out through 3 stages, namely the research preparation stage, research in the classroom, and retrospective analysis. The research was conducted at SMP Negeri 4 Mori Utara with the research subjects totaling 12 students and consisting of three meetings, namely 1) the first meeting: Relation Concept, Relationship Presentation and Domain Concept, Codomain and Range, 2) second meeting: Function Concept, Function Characteristics and Correspondence One-on-one and 3) third meeting: Notation and Function Value. The research instruments used are in the form of learning trajectory hypotheses and data collected through observations, sound recordings, and Student Activity Sheets. The results showed that the learning trajectory in the Relation and Function material with a RME approach designed to improve mathematical problem-solving ability can be applied in the learning process. The resulting learning path is in the form of a flow of activities and activities carried out by students in class in order to achieve the learning goals that have been previously set. Meanwhile, this study was conducted only to see the application of the hypothesis of the learning trajectory of the Relation and Function material in the RME approach.